2019
DOI: 10.21037/jtd.2019.10.37
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital and emergency department pathways of care for exacerbations of chronic obstructive pulmonary disease (COPD)

Abstract: Exacerbations are serious complications of chronic obstructive pulmonary disease (COPD) that often require acute care from pre-hospital and emergency department (ED) services. Despite being a frequent cause of emergency presentations, gaps remain in both literature and practice for emergency care pathways of COPD exacerbations. This review seeks to address these gaps and focuses on the literature of prehospital and ED systems of care and how these intersect with patients experiencing an exacerbation of COPD.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lastly, we found that patients arriving in the ED by ambulance had a higher hospitalization rate. Again, this may reflect disease severity, as an Australian study has found that 78% of AECOPD patients who arrived by ambulance were admitted to the hospital, including 7% who were admitted to the intensive care unit [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found that patients arriving in the ED by ambulance had a higher hospitalization rate. Again, this may reflect disease severity, as an Australian study has found that 78% of AECOPD patients who arrived by ambulance were admitted to the hospital, including 7% who were admitted to the intensive care unit [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…If our results confirm this benefit, we also would like to underscore the importance of training physicians and nurses on the specific medical and care protocols required by patients with ACOPD and APE as already reported in previous studies. 24,26…”
Section: Discussionmentioning
confidence: 99%
“…39 A reported disjunct exists between holistic respiratory ward-based COPD clinical pathways and atomistic acute ED clinical pathways generally due to the difference in care focus, time constraints, national targets, and lack of human and fiscal resources such as beds, clinicians, staff, and high patient turnover (environmental context and resources). 11,15,23,40 Targeted speciality care order sets specifically designed for departmental needs and care focus such as in the ED is highly recommended for implementation. 11,15,41…”
Section: Diagnostic Utilisation Of Spirometry Abg and Oxygen Managementmentioning
confidence: 99%